Desire and Disaster in New Orleans Tourism, Race, and Historical Memory - Thomas, Lynnell L., 1971- (Book collections on Project MUSE., 2014)
Looking at competing representations of race in New Orleans tourism, Lynnell L. Thomas shows how declarations of racial harmony mask the city's history of racial inequality, how popular notions of New Orleans as a site of desire are intertwined with competing ideas of the city as a source of disaster, and how African American tour guides, tour owners, and tourist industry officials have used their own black heritage tours and tourism-focused businesses to challenge exclusionary tourist representations.